On maximal measures with respect to a lattice - James Camacho (International Journal of Mathematics and Mathematical Sciences)
Outer measures are used to obtain measures that are maximal with respect to a normal lattice. Alternate proofs are then given extending the measure theoretic characterizations of a normal lattice to an arbitrary, non-negative finitely additive measure on the algebra generated by the lattice. Finally these general results are used to consider σ-smooth measures with respect to the lattice when further conditions on the lattice hold.